Utilizing E-Commerce for Home Industry Marketing Rujak Mengkudu - Paula Dewanti; Ni Putu Meina Ayuningsih (MITRA: Jurnal Pemberdayaan Masyarakat, 2018)
Mengkudu has been known for a type of fruit that has many health benefits. The targeted partner of our community service was one of rujak mengkudu traditional seller, Ibu Ni Ketut Suji, that is located at Jalan Raya Dalung, Sempidi Village border, subdistrict of Kuta Utara, Badung, Bali, which is approximately 12.5 km from the location of sponsor. By that time, our partner was doing mouth to mouth marketing strategy, in a local scope; direct buyer are those who came to our partner’s house, as well as selling the product in local traditional markets. Such a marketing strategy may be considered a less effective one. Therefore, the initial purpose of this community service was to provide training on the utilization of information technology, especially the utilization of the online marketplace as a marketing media to expand our partner’s business. This community service was conducted by using a demo, best practices and technical guidance. The results of our community service showed that the participants were able to utilize information technology, especially the online marketplace, as a media marketing for their products. This can be measured from the ability of participants which included the ability to create their accounts, use the media interactively, and advertise their products in one of the media online marketplace.